The social and economic importance of sports - Ivan Prudky (Naše gospodarstvo / Our Economy, 2022)
Sports participation does not produce benefits solely on a personal level but also numerous benefits on different societal levels, as well as the level of economies. The paper represents a contribution to the exploration of factors of individuals influencing regularity in sports participation. A logistic regression model was used based on the data from the Eurobarometer special survey from 2018. According to the findings, middle-aged men are the most likely to regularly participate in sports activities and individuals with active socio-professional status are also more likely to practice regular sports activities than individuals who are passive. The same is true for individuals living in less urbanised areas and those with positive life satisfaction compared to those living in urban areas or those who are not satisfied with their life. The results of our research are important for economic policymakers both at the national and regional levels, as well as at the level of individual municipalities. They facilitate the management of sports activities of individuals but are limited to a smaller number of factors with measurement specifics. Suggestions for further research are also presented.
Keywords: Z20; Z28; 330; Sports participation; Sports and social aspects; Sports and economic aspects; Sports policy regulation